The effects of mindfulness upbringing perception on social entrepreneurship orientation: A moderated mediation model of prosocial motivation and perceived pressure from external stakeholders - Shan, Tingting; Tian, Xiaoya (Frontiers in Psychology, 2022)
Driven by a mix of economic and social benefits, social enterprises create new development models that combine wealth creation, social welfare provision and environmental improvement through innovative approaches. Social entrepreneurship orientation reflects the behavioral tendency to transplant entrepreneurship orientation into the field of social value creation, and is a strategy to balance and integrate economic interests and social interests which has a significant impact on social entrepreneurship performance. The purpose of this study is to investigate the internal mechanism through which social entrepreneurs’ mindfulness upbringing perception affects social entrepreneurship orientation. To reveal the internal mechanism, we propose a moderated and mediation model of prosocial motivation and perceived pressure from external stakeholders. Using survey data from social entrepreneurs in China, hierarchical regression analysis and bootstrapping model are adapted to test and verify mediation and moderation effects. The results show that mindfulness upbringing perception indeed positively influence social entrepreneurship orientation directly and partly through the mediating effect of prosocial motivation. Moreover, findings suggest perceived pressure from external stakeholders negatively moderates not only the relationship between prosocial motivation and social entrepreneurship orientation, but also the overall mediation model. This demonstrates that social entrepreneurs in low-level perceived pressure from external stakeholders improve their social entrepreneurship orientation easily when they have high prosocial levels. Based on these findings, we conclude that social entrepreneurship orientation may be achieved more effectively through the complex process of mindfulness upbringing perception, prosocial motivation and perceived pressure from external stakeholders. Finally, the study proposes the theoretical and practical implications and suggestions for follow-up research.